CORAL: Implementing an Open-Source ERM System - Imre, Andrea; Hartnett, Eric; Hiatt, C. Derrik (Taylor & Francis, 2013)
The presenters focused on the benefits and challenges of implementing an open-source electronic resource management (ERM) system called Centralized Online Resource Acquisitions and Licensing (CORAL) at their libraries. Originally developed by the University of Notre Dame’s Hesburgh Libraries, CORAL offers libraries the option to reorganize electronic resource management workflows and collect information about their electronic resources into one central place without having to commit funding for new software from the ever-shrinking library budget. CORAL currently includes four modules: Organizations, Resources, Licensing, and Usage Statistics. In addition to the challenges that are faced in any ERM system implementation, such as collecting and preparing data and training staff, issues specific to using an open-source application in an academic library were presented.
This is an Author's Accepted Manuscript of an Article published in THE SERIALS LIBRARIAN (2013), available online at: http://www.tandfonline.com/doi/abs/10.1080/0361526X.2013.760414.
Keywords: Centralized Online Resource Acquisitions and Licensing (CORAL); electronic resource management; electronic resource management (ERM) system; open source; workflow